The Influence of Internet use on the political participation of youth in Ikeja, Lagos (2018)
This research investigates the influence of the Internet on the political participation of youth in the Ikeja Local Government Area of Lagos state, in Nigeria. The study was hinged on technological determinism; the data was gathered through survey and in-depth interview; through multistage sampling, questionnaires were administered on 600 youth in Ikeja. Findings show that using the Internet over a long period of time will result to some form of political participation. Thus, the youth who use the Internet for a long time are likely to explore other opportunities (like online political participation) offered by the Internet, therefore, the findings of this study will benefit civil liberties organizations, political parties, government agencies and political communication researchers; and suggests that government and political parties should engage the youth more intelligently on political matters through the Internet and make Internet access more affordable.